Cardiac arrest during adult liver transplantation: A single institution's experience with 1238 deceased donor transplants. Issue 11 (10th October 2013) - Matsusaki, Takashi; Hilmi, Ibtesam A.; Planinsic, Raymond M.; Humar, Abhinav; Sakai, Tetsuro
<x xml:space="preserve">Abstract</x> Liver transplantation (LT) is one of the highest risk noncardiac surgeries. We reviewed the incidence, etiologies, and outcomes of intraoperative cardiac arrest (ICA) during LT. Adult cadaveric LT recipients from January 1, 2001 through December 31, 2009 were reviewed. ICA was defined as an event requiring either closed chest compression or open cardiac massage. Cardiac arrest patients who recovered with only pharmacological interventions were excluded. Data included etiologies and outcomes of ICA, intraoperative deaths (IDs) and hospital deaths (HDs), and potential ICA risk factors. ICA occurred in 68 of 1238 LT recipients (5.5%). It occurred most frequently during the neohepatic phase (60 cases or 90%), and 39 of these cases (65.0%) experienced ICA within 5 minutes after graft reperfusion. The causes of ICA included postreperfusion syndrome (PRS; 26 cases or 38.2%) and pulmonary thromboembolism (PTE; 24 cases or 35.3%). A higher Model for End‐Stage Liver Disease (MELD) score was found to be the most significant risk factor for ICA. The ID rate after ICA was 29.4% (20 cases), and the HD rate was 50.0% (34 cases). The 30‐day patient survival rate after ICA was 55.9%, and the 1‐year survival rate was 45.6%: these rates were significantly lower (P < 0.001) than those for non‐ICA patients (97.4% and 85.1%, respectively). In conclusion, the incidence of ICA in adult cadaveric LT was 5.5% with an intraoperative mortality rate of 29.4%. ICA most frequently occurred within 5 minutes after reperfusion and resulted mainly from PRS and PTE. A higher MELD score was identified as a risk factor. Liver Transpl 19:1262–1271, 2013. © 2013 AASLD.